A Color‐tunable Nitride Phosphor for Near‐Ultraviolet Excitation of White Light‐emitting Diodes. Issue 19 (25th August 2022) - Wang, Lixuan; Sun, Dashuai; Lyu, Zeyu; Shen, Sida; Lu, Zheng; Zhao, Hanwei; Wang, Jianhui; You, Hongpeng
Abstract: Due to the diversity of structure and composition and the unique coordination environment, nitride materials enable the doped activator ions to possess compelling luminescence characteristics, such as rich emission colors, favorable stability and tunable emission spectra. Here, novel SrLuSi4 N7 :Ce 3+, Tb 3+ nitride phosphors were successfully synthesized by a modified carbothermal reduction and nitridation method at atmospheric pressure. SrLuSi4 N7 (SLSN) belongs to hexagonal symmetry, with space group P63 mc, and its crystal structure is composed of the basic building block with corner‐sharing [SiN4 ] tetrahedron. Under 365 nm excitation, SLSN:Ce 3+ exhibits a broad emission band peaking at 450 nm with a full width at half‐maximum (FWHM) of 92 nm and the most forceful intensity obtained at the Ce 3+ concentration amount of 0.04. On the basis of the efficient energy transfer, SLSN:Ce 3+, Tb 3+ exhibits color‐tunable emission from blue (450 nm) to green (545 nm). Our results indicate that SLSN nitride phosphor is a promising candidate for near‐ultraviolet (n‐UV) based white LEDs. Abstract : Novel SrLuSi4 N7 :Ce 3+, Tb 3+ nitride phosphors were successfully synthesized at atmospheric pressure using an improved carbon thermal reduction and nitridation method. The first excitation peak of SrLuSi4 N7 :Ce 3+ sample is located at 365 nm, which can be well matched with commercial near‐UV LED chips. On the basis of efficient energy transfer, SLSN:Ce 3+, Tb 3+ exhibits color‐tunable emission from blue (450 nm) to green (545 nm).